2022
DOI: 10.1002/mco2.121
|View full text |Cite
|
Sign up to set email alerts
|

Trained immunity: A Yin‐Yang balance

Abstract: Traditionally, immune memory is regarded as an exclusive hallmark of adaptive immunity. However, a growing body of evidence suggesting that innate immune cells show adaptive characteristics has challenged this dogma. In the past decade, trained immunity, a de facto innate immune memory, has been defined as a long‐term functional reprogramming of cells of the innate immune system: the reprogramming is evoked by endogenous or exogenous insults, the cells return to a nonactivated state and subsequently show alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 150 publications
0
11
0
Order By: Relevance
“…However, trained immunity can also be detrimental in some disease settings. In principle, excessive or chronic activation of innate immune responses by inducing trained immunity could lead to excessive inflammation or immunosuppression during chronic disease [63]. A growing body of research provides evidence that the reprogramming of trained immunity may play a role in the maintenance of a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, trained immunity can also be detrimental in some disease settings. In principle, excessive or chronic activation of innate immune responses by inducing trained immunity could lead to excessive inflammation or immunosuppression during chronic disease [63]. A growing body of research provides evidence that the reprogramming of trained immunity may play a role in the maintenance of a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently it has been shown that innate immunity also plays an important role in immune memory against homologous or even heterologous challenges ( 145 , 146 ). Trained immunity, a de facto innate immune memory, has been defined as a long-term functional reprogramming of the innate immune cells that is evoked by endogenous or exogenous insults, with the cells then returning to a non-activated state and showing altered inflammatory responses against a second challenge ( 147 , 148 ).…”
Section: Latest Findings That Facilitate Tb Vaccine Research Developmentmentioning
confidence: 99%
“…Bacterial and fungal cells and their components (LPS, β-glucan and chitin), virus and parasites are the best-known exogenous ones, but there are other endogenous ones like oxidized low-density lipoprotein, apolipoprotein(a), aldosterone or adrenaline [34]. Since training or tolerizing effects are observed, it must be underscored that TRAIM is a complex delicately balanced mechanism that is only beginning to be understood, and that the same compound, depending on time and concentration might cause opposite effects [53,55].…”
Section: Traim Inductorsmentioning
confidence: 99%
“…Bacterial and fungal cells and their components (LPS, β‐glucan and chitin), virus and parasites are the best‐known exogenous ones, but there are other endogenous ones like oxidized low‐density lipoprotein, apolipoprotein(a), aldosterone or adrenaline [34]. Since training or tolerizing effects are observed, it must be underscored that TRAIM is a complex delicately balanced mechanism that is only beginning to be understood, and that the same compound, depending on time and concentration might cause opposite effects [53, 55]. In this review, we will focus on two examples: on one side, a whole bacterial cell, Mycobacterium bovis inactivated vaccine which would be the closest approach to a natural challenge without its risks, and on the other, one structural component of those types of organism found in bacterial cell wall a broadly known as glycan, an encompassing term grouping large glycosidically bound saccharide polymers including those linked to lipids or proteins, that probably represents the type of true molecular effector of TRAIM present in the former in more complex forms.…”
Section: Traim Inductorsmentioning
confidence: 99%